Forensic Audits in Practice: A Systematic Literature Review - Marnoko Marnoko; Edisah Putra Nainggolan; Ihsan Abdullah (International Journal Of Economics Social And Technology, 2026)
This study aims to explore and synthesize literature related to the role of forensic audits in fraud detection and prevention through the Systematic Literature Review (SLR) approach. Article searches were conducted on Scopus, Web of Science, Google Scholar, and JSTOR databases using keywords such as "forensic audit", "fraud detection", and "forensic accounting", which yielded 320 articles. After the selection process using the PRISMA diagram, 15 high-quality articles were further analyzed. The results of the review show that technologies such as machine learning, big data analytics, and blockchain have contributed significantly to improving the effectiveness of fraud detection, especially through the identification of transaction anomalous patterns. However, key challenges include the high cost of technology adoption, a lack of consistent regulation and professional standards, as well as the competency gap of forensic auditors especially in terms of professional skepticism. The application of forensic audits is also increasingly relevant in the digital sector such as digital banking and insurance. This study concludes that although forensic audits have great potential, there is a need to strengthen regulations, improve auditor competency training, and provide more accessible technology to optimize fraud detection and prevention in an ongoing manner.